Reviewing proceedings of the II International Conference “Metabolic Syndrome and Dyslipidemia”, New York: how to adapt largeD scale studies' results to realDworld clinical settings in Russia? - M. N. Mamedov (Российский кардиологический журнал, 2005)
.